Clinicopathological study of leiomyomas in hysterectomy specimens - Kaur, Manpreet; Gupta, Rajiv Kamal; Kaur, Simrat Jit; Kaur, Panchampreet (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Leiomyomas are benign tumors of smooth muscle cells commonly encountered in women of reproductive age group. Aim of this study was to conduct a histopathological study of leiomyomas in hysterectomy specimens and to correlate them with clinical findings. Methods: A prospective study was done on 130 hysterectomy specimens clinically diagnosed as leiomyoma. The specimens were subjected to histopathological examination. Results: In this study, the most common age group was 31-50 years (87.69%). Most common complaint was menorrhagia (51.54%). In endometrium, the most common histopathological diagnosis was proliferative phase (46.15%) followed by endometrial hyperplasia (19.23%). The most common secondary change was hyalinization and the most common site was intramural (62.9%). Conclusions: Hysterectomy is a commonly performed procedure in the management of uterine leiomyomas. The ultimate diagnosis and prognosis depends on the histopathological examination; therefore, every operated specimen must be subjected to histopathology.